(untitled) (Journal of Ethics in Emerging Technologies & Society p-ISSN 3117-5996 and e-ISSN 3117-6003, 2025)
Trust and accountability in autonomous robotic systems are foundational requirements for socially beneficial deployment of robotics across healthcare, logistics, eldercare, manufacturing, and public infrastructure domains. Trust – the human willingness to accept vulnerability to robotic system behaviour – is both a prerequisite for adoption and a potential risk: inappropriate trust (over-reliance) is as ethically problematic as inappropriate distrust (under-utilisation). Accountability – the institutional and technical mechanisms through which responsibility for robotic system harms is assigned, verified, and remedied – is challenged by autonomous systems whose behaviour emerges from trained models rather than explicit programming, creating novel accountability gaps. This paper proposes the Robot Trust and Accountability Framework (RoTAF), a systematic analysis of five trust dimensions and four accountability mechanisms across six robotic deployment contexts: surgical robots, eldercare robots, autonomous warehouse systems, delivery drones, collaborative manufacturing robots, and autonomous emergency response robots. RoTAF introduces the Trust-Accountability Quality Score (TAQS) and evaluates current governance adequacy across all six contexts. Key results: eldercare robots achieve the lowest TAQS (0.484) due to emotional dependency risk and dignity concerns; surgical robots achieve the highest TAQS (0.724) driven by strong medical accountability frameworks; over-trust is the most prevalent trust pathology across all contexts. The framework provides trust calibration and accountability design guidance.